The interplay of autonomous and controlled motivation in youth team sports - Rottensteiner, C.; Happonen, L.; Konttinen, N. (International Journal of Sport Psychology, 2015)
The present study was designed to examine the interplay of autonomous and controlled motivation, and their relations to perceived physical competence, amount of practice, and enjoyment among youth athletes. The problem setting was based upon the self-determination theory (SDT) and hierarchical model of intrinsic and extrinsic motivation (HMIEM). Participants (N = 1936) for the study included 15-year-old team sport athletes involved in soccer, ice-hockey, and basketball. They completed a survey questionnaire which included Sport Motivation Scale, Perceived Physical Competence Scale, and Enjoyment Scale. Participants were also asked to evaluate their weekly amount of sport practice. Based on cluster analysis, four different motivational subgroups were identified: 1) high autonomous (AU) - high controlled (C) profile, 2) moderate AU - low C profile, 3) moderate AU - moderate C profile, and 4) low AU - low C profile. The participants in groups 1 and 2 reported higher levels of physical competence, practiced more, and experienced greater enjoyment towards their sport than the participants in group 3 and 4. The present data suggest that the interplay of autonomous and controlled motivation can affect perceived physical competence, the amount of practice, and enjoyment among young team sport athletes. In contrast to the SDT and HMIEM, enhanced controlled motivation did not result in negative consequences, provided that autonomous motivation was also in high level. Moderate levels of autonomous motivation did not lead to positive consequences, if controlled motivation was at the same time also in moderate level.